Change of carotid intima‐media thickness is associated with age in elderly Japanese patients without a history of cardiovascular disease. Issue 8 (14th October 2014) - Watanabe, Kentaro; Ouchi, Motoshi; Ohara, Makoto; Kameda, Wataru; Susa, Shinji; Oizumi, Toshihide; Wada, Manabu; Suzuki, Tatsuya; Kawanami, Toru; Oba, Kenzo; Kato, Takeo
<x xml:space="preserve">Abstract</x> Aim The present study aimed to evaluate the relationship between the change of carotid intima‐media thickness (CIMT) and clinical characteristics in Japanese patients without a history of cardiovascular disease. Methods The study participants were 149 Japanese patients without a history of cardiovascular disease treated in our outpatient department. The in all participants CIMT was measured with ultrasonography at baseline and after a mean interval of 2.4 years. Study participants were divided into a middle‐aged group (younger than 65 years: n = 59) and an elderly group (65 years or older: n = 90). The annual CIMT change (ΔCIMT) was calculated, and the associations between ΔCIMT and clinical characteristics, including age, were evaluated in both groups. Results The ΔCIMT was significantly correlated with age in all participants (r = 0.222; P < 0.05) and in elderly participants (r = 0.234; P < 0.05), but was not correlated with other risk factors. The annual ΔCIMT was significantly higher in elderly participants (0.015 ± 0.096 mm) than in middle‐aged participants (–0.018 ± 0.088 mm; P < 0.05). Multivariate linear regression analysis with ΔCIMT as a dependent variable and risk factors as independent variables showed that ΔCIMT was significantly associated with age in all participants (β = 0.002; P < 0.05) and in elderly participants (β = 0.004; P < 0.05), but not with other risk factors. Conclusions Annual CIMT change is associated with age, rather than with other clinical characteristics, including traditional cardiovascular risk factors, such as diabetes and hypertension, in elderly Japanese patients without a history of cardiovascular disease. Geriatr Gerontol Int 2015; 15: 1023–1030.